Pengaruh Media Informasi Kesehatan Menggunakan Leaflet Tentang Penyakit Influenza terhadap Tingkat Pengetahuan Pasien di Apotek Ngudi Waluyo Ungaran - Avian Tri Wahyudi; Arif Arika Sendi; Siti Qoyimah; Niken Dyahariesti; Jatmiko Susilo (PPNI UNIMMAN, 2025)
This study aims to analyze the effect of the use of Health Information Media in the form of leaflets on the level of patient knowledge about influenza in pharmacies Ngudi Waluyo, Ungaran. Leaflet Media is used as an educational tool to improve patient understanding related to influenza, including aspects of causes, symptoms, complications, and management and treatment. The type of research used is quasi experiment with pre-test and post-test design, involving 94 respondents who meet the inclusion criteria. Data analysis was conducted using the Wilcoxon statistical test to determine the difference in the level of knowledge of patients before and after education. The results showed a significant increase in the level of knowledge of patients after obtaining education using leaflets. Before being given education, respondents with a good knowledge level category were 56.7%, and increased to 96.8% after providing education, with a value of p = 0.001 (p < 0.05) which showed a significant difference between the two measurements. Thus, the Health Information media in the form of leaflets proved effective in increasing patient knowledge about influenza and can be used as an alternative educational media that is simple, practical, and efficient in supporting pharmaceutical services in pharmaceutical service facilities.